The Implementation of STEM-Based Lipid E-Book on Student Learning Outcomes - Dewi Handayani; Muzanip Alperi; Mellyta Uliyandari (Journal of Educational Chemistry (JEC), 2022)
The purpose of the study  was to analyze the effect of using lipid e-books using the STEM approach on student learning outcomes. The method uses pre-experimental research with one group pretest posttest design. This research was conducted at one of the State Universities in Bengkulu with the subject consisting of 26 students who took the Organic Chemistry 2 course. The instrument used in this study was a multiple choice test with 4 meetings in the form of pretest and posttest questions. Data analysis techniques include the average value (mean), normality test, and hypothesis testing using a t-test using the SPPS for windows version 23 computer program. The results showed the average score of the learning outcomes before using the lipid organic chemistry e-book was 54.90, while after using the e-book the average value is 79.81. The learning outcomes data were normally distributed and the t-test value showed Significant (2-tailed) 0.00. These results indicate that the developed STEM-based teaching materials can improve student learning outcomes in particular and are able to improve the quality of learning for organic chemistry 2 courses in general.